Health Impacts of Pesticide Exposure Among Farmers: A Systematic Review and Implications for Agronursing Practice - Enggal Hadi Kurniyawan; Dicky Endrian Kurniawan; Kholid Rosyidi Muhammad Nur; Alfid Tri Afandi; Yeni Fitria; Emi Wuri Wuryaningsih; Robby Prihadi Aulia Erlando (Health and Technology Journal (HTechJ), 2026)
Pesticide exposure among farmers poses significant health risks globally; however, comprehensive recent evidence on the role of nursing in mitigating these hazards remains underexplored. This systematic review aims to synthesize empirical findings from 2024 to 2025 on the health impacts of pesticide exposure in farming populations and discusses implications for agronursing practice. Following the PRISMA 2020 guidelines, a systematic search was conducted across Scopus, PubMed, and ProQuest using the keywords "pesticide," "farmer," and "nursing." From an initial pool of 2,757 records, 10 original research articles published between 2024 and 2025 met the inclusion criteria: full-text, English-language, open-access, peer-reviewed research articles with ethical clearance, an active DOI, and no study design restrictions beyond excluding non-original works. The 10 included studies were conducted in Thailand, Spain, Greece, Ethiopia, Indonesia, Türkiye, and India. These studies revealed consistent associations between pesticide exposure and adverse health outcomes, including sleep disorders, depression, suicide attempts, oxidative stress, DNA damage, elevated inflammatory markers, and increased stroke risk biomarkers. Behavioral assessments indicated widespread deficiencies in safe pesticide handling and low risk perception. Importantly, nurse-led interventions demonstrated effectiveness in improving occupational health service delivery and farmer knowledge. Pesticide exposure continues to pose a risk to farmers' health across diverse global settings. Agronursing emerges as a vital interdisciplinary approach to address this challenge through education, early detection, advocacy, and community-based prevention. Integrating agronursing competencies into primary healthcare and nursing curricula is crucial for protecting agricultural workers and promoting sustainable rural health.